Surface Modification Analysis of Dental Implant Materials through Taguchi and RSM Approach for: A Review - Singh, Sarabjit (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 10 No 1&2 (2023): Journal of Advanced Research in Instrumentation and Control Engineering, 2023)
Dental implants have revolutionized the field of dentistry, providing a durable and long-lasting replacement for missing teeth. The success of dental implants is highly dependent on the materials used and their properties, including surface characteristics. In recent years, Taguchi and Response Surface Methodology (RSM) techniques have emerged as powerful tools for optimizing surface modification parameters to improve dental implant materials. This review paper provides a comprehensive overview of Taguchi and RSM methods for surface modification analysis of dental implant materials. The paper explains the principles behind Taguchi and RSM techniques and their application to dental implant materials. The advantages and limitations of each technique are highlighted, and recent advances in the field are discussed. The paper presents case studies and examples demonstrating the effectiveness of Taguchi and RSM techniques in optimizing surface properties of dental implant materials. By optimizing the surface properties, it is possible to improve the biocompatibility, osseointegration, and corrosion resistance of dental implant materials, resulting in better clinical outcomes. Keywords: Taguchi, Response Surface Methodology (RSM), surface modification, dental implant materials, optimization parameters. How to cite this article: Singh S. Surface Modification Analysis of Dental Implant Materials through Taguchi and RSM Approach for: A Review. J Adv Res Instru Control Engi 2023; 10(1): 6-9